4H / fcc unconventional phase platinum-based nanomaterial for electrocatalytic alcohol oxidation

By epitaxially growing platinum-based nanobranches on 4H/fcc gold nanorods to form core-shell heterostructures, the problem of preparation of platinum-vana and platinum-titanium alloys in the prior art is solved, and efficient preparation and catalytic performance under mild conditions is achieved promote.

CN119181815APending Publication Date: 2024-12-24CITY UNIV OF HONG KONG SHENZHEN RES INST
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410453840.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-06-21
Filing Date
2024-04-16
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The difficulty in the effective preparation of unconventional platinum-based nanomaterials with controllable composition and morphology under mild conditions, especially platinum vanadium and platinum titanium alloys, limiting their potential in catalytic applications.

Method used

By epitaxially growing platinum-based nanobranches on 4H/fcc gold nanorods, core-shell heterostructures such as Au-Pt, Au-PtV and Au-PtTi are formed. A simple two-step wet chemistry method is used to adjust the reaction conditions to control the shape appearance and nature.

Benefits of technology

It has achieved efficient preparation of unconventional phase platinum-based nanomaterials with excellent catalytic properties under mild conditions, and is suitable for applications such as direct alcohol fuel cells, significantly improving the activity and stability of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119181815A_ABST
    Figure CN119181815A_ABST
Patent Text Reader

Abstract

Provided herein is a 4H / fcc unconventional phase platinum-based nanomaterial for electrocatalytic alcohol oxidation, which can be used as a heterogeneous catalyst for alcohol oxidation reactions in direct alcohol fuel cell anodic reactions. The heterogeneous catalyst includes at least one platinum-based nanobranch deposited on gold nanorods by using a synthesis process to form a 4H / face-centered cubic (fcc) unconventional phase. The synthesis process includes the steps of: mixing a material A selected from platinum (II) bis (acetylacetonate), vanadium (III) acetylacetonate, and titanium oxide acetylacetonate with a solvent B selected from oleylamine and 1-octadecene to form a first mixture; adding a dispersion C of 4H / fcc gold nanorods to the first mixture to form a second mixture wherein the ratio of A to B is in the range of 0.5 to 2 and the ratio of A to C is in the range of 2 to 6; heating the second mixture; and recovering a 4H / fcc platinum-based heterostructure containing gold from the second mixture.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention generally relates to phase engineering of nanomaterials (PEN) technology; more particularly, the present invention relates to PEN technology for epitaxially growing 4H / face-centered cubic (fcc) unconventional phase platinum-based nanomaterials on nanorods. Background Art

[0002] Noble metal heterostructures with controllable composition, morphology, and interface have been extensively studied due to their outstanding performance in various applications such as catalysis and plasma. Among the various strategies for synthesizing noble metal heterostructures, seeded epitaxial growth is considered to be one of the most promising methods to achieve precise control over their chemical composition and morphology. In addition, seeds with different metal compositions can effectively change the lattice parameters and electronic configurations of the secondary metals, ultimately regulating the properties and functions of the heterostructures. For example, the overgrowth of an excess of platinum shells on palladium-based nanocubes leads to the formation of core-shell heterostructures, in which the lattice structure of platinum can be regulated by the lattice expansion and contraction of the seeds. Therefore, the lattice changes can adjust the d-band center of platinum and also regulate the catalytic performance. However, previous studies have mainly focused on seeds with thermodynamically stable phases to achieve the controllable epitaxial growth of noble metal-based heterostructures for promising applications.

[0003] The concept of phase engineering of nanomaterials (PEN) has been recently proposed, which enables the construction of unconventional phase heterostructures based on noble metals by seeded epitaxial growth. PEN provides opportunities for the synthesis of noble metal heterostructures with unconventional crystalline phases (including heterophases) to achieve efficient catalysis. However, it is still a challenge to prepare heterophase noble metal-based heterostructures with controllable composition and morphology, and further study the influence of their structure on catalytic performance.

[0004] More importantly, PEN demonstrates that the properties and functions of noble metal heterostructures can be effectively tuned by regulating the crystalline phase. In particular, noble metal-based unconventional phase heterostructures have great potential in various applications due to the existence of unconventional phases, phase boundaries, and synergistic effects between different crystalline phases. For example, epitaxial growth of ruthenium on 4H / face-centered cubic (fcc) gold nanowires and epitaxial growth of palladium on fcc-2H-fcc gold nanorods can construct 4H / fcc core-shell Au@Ru nanowires and fcc-2H-fcc core-shell Au@Pd nanorods, respectively. The lattice mismatch between the seed and secondary metals and the presence of unconventional phases can change the electronic configuration of the heterostructures, thereby tuning the catalytic performance. However, in many previous studies, the thermodynamic instability of unconventional phases has led to great challenges in tuning the morphology of unconventional phase noble metal heterostructures, which has limited the understanding of structure dependence.

[0005] Platinum-based nanomaterials are widely considered as promising catalysts for various applications, such as oxygen reduction reaction (ORR) and alcohol oxidation reaction (AOR) in direct alcohol fuel cells (DAFCs). To date, considerable efforts have been made to construct high-performance platinum-based catalysts with precise control of their composition, size, and morphology. For example, PtPb@Pt core-shell nanosheets exhibit enhanced ORR electrocatalytic activity compared with commercial Pt / C, PtPb nanoparticles, and PtPb nanosheets, due to the lattice structure of the platinum shell that can be compressed and expanded along different axes simultaneously. However, the crystalline phase of platinum-based nanomaterials plays a crucial role in determining their intrinsic physicochemical properties, but these are rarely mentioned. In addition, the introduction of transition metals (such as nickel, cobalt, etc.) into platinum to construct platinum-based alloys has been shown to be a promising approach to reduce the amount of platinum used and further improve its catalytic performance. However, due to their large negative reduction potentials, the addition of early transition metals (such as vanadium and titanium) to platinum usually requires harsh conditions and has therefore been rarely studied. In order to synthesize platinum alloys containing early transition metals (such as platinum-vanadium and platinum-titanium) under mild wet chemical conditions, and considering that heterogeneous nucleation requires lower activation energy than homogeneous nucleation, seeded epitaxial growth may be an effective strategy.

[0006] However, as mentioned above, the preparation of unconventional phase nanomaterials remains challenging due to their thermodynamically unstable nature. For example, although platinum-based alloys containing early transition metals such as titanium and vanadium have shown great application potential, this is usually prepared under harsh and difficult conditions and has not been commercialized. Therefore, it is necessary to develop a preparation method for unconventional phase nanomaterials that can effectively address these challenges. Summary of the invention

[0007] The purpose of the present invention is to provide a device and method to solve the defects and unmet needs in the prior art.

[0008] According to one aspect of the present invention, a heterogeneous catalyst for alcohol oxidation reaction in a direct alcohol fuel cell anode reaction is provided. The heterogeneous catalyst comprises at least one platinum-based nanobranch structure, which is deposited on gold nanorods by using a synthesis process to obtain a 4H / face-centered cubic (fcc) unconventional phase in an epitaxial growth manner. The synthesis process includes the following steps: mixing a material A selected from platinum (II) bis (acetylacetonate), vanadium (III) acetylacetonate and titanium oxide acetylacetonate with a solvent B selected from oleylamine and 1-octadecene to form a first mixture; adding a dispersion C of 4H / fcc gold nanorods to the first mixture to form a second mixture, wherein the contents of A, B and C are all positive values, the ratio of A to B is in the range of 0.5 to 2, and the ratio of A to C is in the range of 2 to 6; heating the second mixture to a temperature in the range of 150°C to 200°C and the duration is in the range of 5 hours to 15 hours; and recovering the 4H / fcc platinum-based heterostructure nanorods containing gold from the second mixture.

[0009] According to one aspect of the present invention, platinum-based nanobranch are epitaxially grown from gold nanorods, thereby forming a 4H / fcc core-shell Au-Pt-based heterostructure with gold nanorods as seeds.

[0010] According to one aspect of the present invention, the platinum-based nanorods further include vanadium, which is epitaxially grown from the gold nanorods to form a 4H / fcc core-shell Au-PtV heterostructure with the gold nanorods as seeds.

[0011] According to one aspect of the present invention, the platinum-based nanorods further include titanium, which is epitaxially grown from the gold nanorods to form a 4H / fcc core-shell Au-PtTi heterostructure with the gold nanorods as seeds.

[0012] According to one aspect of the present invention, the platinum-based nanorods further include vanadium, which is epitaxially grown from the gold nanorods to form a 4H / fcc unconventional phase core-shell Au-PtV heterostructure with the gold nanorods as seeds.

[0013] According to one aspect of the present invention, the platinum-based nanorods further include titanium, which is epitaxially grown from the gold nanorods to form a 4H / fcc unconventional phase core-shell Au-PtTi heterostructure with the gold nanorods as seeds.

[0014] The synthesis strategy for heterogeneous catalysts proposed in the present invention is a simple and two-step method that can adapt to mild reaction conditions. This method has several advantages, including avoiding harsh conditions, reducing costs and improving reproducibility. In addition, this synthesis method can be easily scaled up by increasing the amount of reactants and the volume of the reactor, making it suitable for large-scale production of unconventional phase platinum-based nanomaterials. In addition, this synthesis strategy is a general method that can be used to prepare shape-controlled unconventional phase platinum and platinum-early transition metal alloys. Unconventional phase platinum-based nanomaterials are synthesized under mild conditions by using 4H / fcc gold nanorods as seeds. In addition, the morphology of platinum vanadium and platinum titanium alloys grown on gold nanorods can also be adjusted by simply modifying the reaction conditions. The resulting 4H / fcc unconventional phase platinum-based nanomaterials can be used as heterogeneous catalysts for new electrocatalytic alcohol oxidation reactions, which can play an important potential in various industrial fuel cell applications. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Embodiments of the present invention are described in more detail below, with reference to the following drawings:

[0016] Figure 1 To show the characterization diagram of 4H / fcc gold nanorods according to some embodiments of the present disclosure;

[0017] Figure 2 To show the characterization diagram of 4H / fcc Au@Pt heterostructure according to some embodiments of the present disclosure;

[0018] Figure 3 is an exemplary X-ray photoelectron spectroscopy (XPS) spectrum of 4H / fcc Au@Pt heterostructure;

[0019] Figure 4 The characterization diagram of 4H / fcc core-shell Au@PtV heterostructure according to some embodiments of the present disclosure is shown;

[0020] Figure 5 Showing a characterization diagram of a product according to some embodiments of the present disclosure;

[0021] Figure 6An exemplary X-ray diffraction (XRD) pattern of a product according to some embodiments of the present disclosure is shown;

[0022] Figure 7 Showing further characterization diagrams of products according to some embodiments of the present disclosure;

[0023] Figure 8 An exemplary XPS spectrum of a 4H / fcc core-shell Au@PtV heterostructure according to some embodiments of the present disclosure is shown;

[0024] Fig. 9 Showing a characterization diagram of a 4H / fcc Au@PtV heterostructure according to some embodiments of the present disclosure;

[0025] Fig.10 Showing further characterization diagrams of products according to some embodiments of the present disclosure;

[0026] Fig.11 Showing further characterization diagrams of products according to some embodiments of the present disclosure;

[0027] Fig.12 Showing further characterization diagrams of products according to some embodiments of the present disclosure;

[0028] Fig.13 An example XPS spectrum of 4H / fcc Au@PtV heterostructure is presented;

[0029] Fig.14 A comparison diagram of exemplary XPS spectra of platinum 4f energy spectrum peaks of 4H / fcc Au@Pt and 4H / fcc Au@PtV heterostructures according to some embodiments of the present disclosure is shown;

[0030] Fig.15 Showing a characterization diagram of a 4H / fcc Au@PtTi heterostructure according to some embodiments of the present disclosure;

[0031] Fig.16 An exemplary XPS spectrum of a 4H / fcc core-shell Au@PtTi heterostructure according to some embodiments of the present disclosure is shown;

[0032] Fig.17 Showing further characterization diagrams of 4H / fcc Au@PtTi heterostructures according to some embodiments of the present disclosure;

[0033] Fig.18 An exemplary XPS spectrum of a 4H / fccAu@PtTi heterostructure according to some embodiments of the present disclosure is shown;

[0034] Fig.19presenting exemplary results of electrochemical measurements according to some embodiments of the present disclosure;

[0035] Fig. 20 An example graph of a cyclic voltammetry (CV) curve according to some embodiments of the present disclosure is shown;

[0036] Fig.21 Showing a durability evaluation diagram of a 4H / fccAu@PtV heterostructure according to some embodiments of the present disclosure;

[0037] Fig. 22 Showing a characterization diagram of a 4H / fccAu@PtV heterostructure according to some embodiments of the present disclosure;

[0038] Fig.23 Showing exemplary result graphs of electrochemical measurements according to some embodiments of the present disclosure;

[0039] Fig.24 Showing exemplary result graphs of electrochemical measurements according to some embodiments of the present disclosure;

[0040] Fig.25 The in-situ infrared reflection absorption spectroscopy study of the electrochemical MOR of 4H / fcc Au@Pt nanorods according to some embodiments of the present disclosure is presented;

[0041] Fig.26 The XRD characterization diagram of 4H / fcc gold nanorods according to some embodiments of the present disclosure is shown;

[0042] Fig. 27 A flow chart illustrating an overall method for synthesizing a heterogeneous catalyst for an alcohol oxidation reaction in a direct alcohol fuel cell anode reaction according to some embodiments of the present disclosure. DETAILED DESCRIPTION

[0043] In the following description, platinum-based nanomaterials grown on nanorods and the like will be used as preferred examples. For skilled technicians, modifications, including additions and / or substitutions, can be made without departing from the scope and spirit of the present invention. In order not to obscure the present invention, specific details may be omitted; however, the present invention is to enable skilled technicians to implement the contents taught herein without excessive experiments.

[0044] In the present disclosure, a simple, two-step wet chemical method is provided for achieving a control method and preparation method for 4H / fcc unconventional phase platinum and platinum early transition metal alloy nanomaterials. All starting chemicals including solvents, precursors and surfactants can be obtained from commercial sources. In short, the method for synthesizing 4H / fcc unconventional phase platinum-based nanomaterials includes the use of oleylamine, 1-octadecene, noble metal salts, ascorbic acid and tetrabutylammonium bromide. By simply adjusting the reaction conditions, the morphology of 4H / fcc platinum vanadium and platinum titanium alloys on a gold template can be adjusted to produce a core-shell morphology. A method for preparing 4H / fcc unconventional phase platinum and platinum early transition metal alloys by an epitaxial growth process is provided. By using 4H / fcc gold nanorods as seeds, 4H / fcc Au@Pt (i.e., gold (Au) as the core and platinum (Pt) as the shell), 4H / fcc Au@PtV (i.e., gold (Au) as the core and platinum vanadium (PtV) as the shell), and 4H / fcc Au@PtTi (i.e., gold (Au) as the core and platinum titanium (PtTi) as the shell) heterostructures can be constructed. In addition, the morphology of 4H / fcc Au@PtV and 4H / fcc Au@PtTi heterostructures can be further tuned by precisely controlling the reaction conditions, thereby producing core-shell structures.

[0045] The combination of platinum precursors and ligand-forming solvents such as oleylamine can be used to precisely control the nanostructure without being limited by the growth mechanism. Oleylamine is a positively charged, strongly coordinating solvent that can tightly bind to the metal precursor to form a homogeneous solution. Oleylamine may also form complexes (e.g., ligand complexes) with the metal ions of the precursor. As a result, metastable materials may be formed that can serve as secondary precursors and thus decompose in a controlled manner, thereby regulating the structure of the product.

[0046] Oleylamine may act as a cationic surfactant to ensure uniform dispersion of platinum. When the first mixture is added to the second mixture, negatively charged particles are first formed, and the ligands are stabilized by positively charged oleylamine on both sides through electrostatic effects. The oleylamine solvent can prevent material aggregation and thickness growth along the Z direction, thereby forming the desired island structure. In addition, oleylamine can also stabilize the crystal structure of the product.

[0047] 4H / fcc Au@Pt heterostructures, 4H / fcc Au@PtV heterostructures, and 4H / fcc Au@PtTi heterostructures can be synthesized by using 4H / fcc gold nanorods as seeds. Figure 1 The characterization diagram of 4H / fcc gold nanorods according to some embodiments of the present disclosure is shown, wherein Figure 1 Part (a) is an example scanning electron microscope (SEM) image of 4H / fcc gold nanorods; Figure 1Part (b) is an exemplary low-resolution transmission electron microscopy (TEM) image of 4H / fcc gold nanorods; Figure 1 Part (c) is an exemplary TEM image of a typical gold nanorod; Figure 1 Part (d) is Figure 1 An exemplary high-resolution TEM image of the area marked by the white box in part (c), which shows abundant 4H and fcc-twin structures.

[0048] The synthesis process of 4H / fcc gold nanorods will be provided below.

[0049] In some embodiments of the synthesis process involving the synthesis of 4H / fcc gold nanorods, 3.2 ml of 2-methylcyclohexylamine and 6.8 ml of oleylamine (OAm) are first mixed in a 40 ml glass bottle to form a uniform solution, which is referred to as solution A. Then, 30.0 mg of HAuCl4 is added to the glass bottle containing solution A, and then N2 gas is passed into the solution to remove air. After sealing the glass bottle with polytetrafluoroethylene (PTFE) tape and Parafilm (a film material made of a mixture of polyethylene and plant wax), the mixture is vortexed until the HAuCl4 is completely dissolved. Then, the obtained uniform solution is heated to 70°C in an oil bath and reacted for 8 hours. After the reaction is completed, the deep red product is washed three times with a mixture of hexane and ethanol and redispersed in 3.0 ml of hexane to obtain 4H / fcc gold nanorods dispersed in hexane.

[0050] The synthesis process of 4H / fcc Au@Pt heterostructures will be provided below.

[0051] In some embodiments of the synthesis process involving the synthesis of 4H / fcc Au@Pt heterostructures, 2.0 mg of diacetylacetonate platinum (II) (Pt(acac)2) and 20.0 mg of L-ascorbic acid are first added to a 15 mL Schlenk tube containing 2.0 mL of oleylamine. Subsequently, the mixture is sonicated for 30 minutes. Then, 0.75 mL of 4H / fcc gold nanorods dispersed in hexane prepared in advance are added to the solution. The Schlenk tube is evacuated at room temperature for 30 minutes and then passed with N2 gas under magnetic stirring. Then, the mixture is heated to 170°C and maintained for 5 hours. Finally, the resulting product is washed with a mixture of hexane and ethanol three times for 3 minutes each time by centrifugation at 5000 rpm. The resulting 4H / fcc core-shell Au@Pt nanorods are dispersed in hexane again for further characterization.

[0052] In one embodiment, 4H / fcc Au@Pt heterostructures can be synthesized using platinum (II) diacetylacetonate as a metal precursor, oleylamine as a solvent and surfactant, L-ascorbic acid as a reducing agent, and 4H / fcc gold nanorods as seeds.

[0053] Regarding the said characterization, Figure 2 The characterization diagram of 4H / fcc Au@Pt heterostructure according to some embodiments of the present disclosure is shown, wherein Figure 2 Part (a) is an exemplary TEM image of 4H / fcc Au@Pt nanorods; Figure 2 Part (b) is an exemplary TEM image of a typical 4H / fcc Au@Pt nanorod; Figure 2 Part (c) is an exemplary scanning transmission electron microscopy (STEM) image of 4H / fcc Au@Pt nanorods and the corresponding energy dispersive X-ray spectroscopy (EDS) elemental distribution map; Figure 2 Part (d) is an exemplary EDS line scan profile on a single 4H / fcc Au@Pt nanorod marked by a white line in part (c); Figure 2 Part (e) is an exemplary spherical aberration corrected high-resolution HAADF-STEM image of a typical 4H / fcc Au@Pt nanorod; Figure 2 Parts (e1)-(e4) are exemplary FFT images obtained from the corresponding dashed boxes in part (e); Figure 2 Part (f) is an exemplary integrated pixel intensity of gold Au (taken from the oblique rectangles in the partial area (e1)) and platinum Pt (taken from the oblique rectangles in the partial area (e2)) along the

[0004] 4H direction. Figure 3 is an exemplary X-ray photoelectron spectroscopy (XPS) pattern of a 4H / fcc Au@Pt heterostructure, showing the gold Au 4f spectrum peak in part (a) and the platinum 4f spectrum peak in part (b).

[0054] Specifically, in Figure 2 The TEM images of parts (a) and (b) show the morphology of the prepared 4H / fcc Au@Pt nanorods. It can be seen in the figure that there is a uniform platinum shell with an average thickness of 4.7±0.5 nm on the gold nanorods. STEM-EDS elemental image ( Figure 2 (c) of the figure) and the line scan ( Figure 2 Part (d) of Figure 3 shows the atomic distribution of gold and platinum, which confirms the formation of the core-shell heterostructure. The atomic arrangement of the 4H / fcc Au@Pt heterostructure was studied using spherical aberration-corrected HAADF-STEM. Figure 2As shown in (e), the continuous lattice fringes extending from the gold core to the platinum shell clearly indicate the epitaxial growth relationship. Figure 2 The fast Fourier transform (FFT) patterns of parts (e1), (e2), (e3), and (e4) show that both gold and platinum have 4H / fcc unconventional phase structures. In addition, Figure 2 Part (f) shows the integrated pixel intensity of the (0004)4H lattice, where the average lattice spacing of (0004)4H is calculated from the e1 region of the gold nanorod. Change to the e2 region of the platinum shell The atomic ratio of gold to platinum was determined to be 69.4:30.6 by inductively coupled plasma-optical emission spectroscopy (ICP-OES). In addition, X-ray photoelectron spectroscopy (XPS) was performed to study the electronic structure of gold and platinum. The results are shown in Figure 3 The peaks of gold 4f and platinum 4f in the XPS spectrum confirm that the gold and platinum elements in the 4H / fcc Au@Pt heterostructure are in the metallic state.

[0055] The synthesis procedures of core-shell Au@PtV and Au@PtTi heterostructures will be provided below.

[0056] In some embodiments involving the synthesis of core-shell Au@PtV heterostructures, 2.0 ml of 1-octadecene (ODE) and 2.0 ml of OAm are first mixed in a 15 ml Schlenk tube. Then 2.0 mg of Pt(acac)2, 4.0 mg of vanadium(III) acetylacetonate (V(acac)3), and 20.0 mg of L-ascorbic acid are added to the solution. Subsequently, the mixture is ultrasonically treated for 30 minutes. Then, 2.0 mg of tetraoctylammonium bromide (TOAB) and 0.75 ml of 4H / fcc gold nanorods dispersed in hexane are added to the solution. The Schlenk tube is evacuated at room temperature for 30 minutes and ventilated with nitrogen gas under magnetic stirring. Then, the mixture is heated to 180°C and maintained for 5 hours. Finally, the obtained product is washed 3 times with a mixture of hexane and ethanol under centrifugation conditions at 5000 rpm for 3 minutes each time. The resulting 4H / fcc core-shell Au@PtV heterostructures were dispersed again in hexane for further characterization. In some embodiments involving the synthesis of core-shell Au@PtTi heterostructures, the synthesis conditions of 4H / fcc core-shell Au@PtTi are similar to those of Au@PtV nanostructures, except that V(acac)3 is replaced by acetylacetonate titanate and the reaction temperature is increased to 185°C.

[0057] The synthesis process of core-shell heterostructures hierarchical Au@PtV and Au@PtTi will be provided below.

[0058] In some embodiments of the synthesis process involving core-shell heterostructure Au@PtV, 2.0 mg of Pt(acac)2 and 3.0 mg of V(acac)3 are first added to a 15 mL Schlenk tube containing 2.0 mL of OAm. Subsequently, the mixture is sonicated for 30 minutes. Then, 5.0 mg of TOAB and 0.75 mL of prepared 4H / fcc gold nanorods dispersed in hexane are added. The Schlenk tube is evacuated for 30 minutes at room temperature and under magnetic stirring to remove the hexane. The mixture is heated to 190°C and maintained for 12 hours. Finally, the obtained product is centrifuged and washed three times with a mixture of hexane and ethanol, each time at a speed of 5000 rpm and a time of 3 minutes. The obtained sample will be redispersed in hexane for further characterization. In some embodiments involving the synthesis process of core-shell heterostructure Au@PtTi, the synthesis conditions of 4H / fcc core-shell heterostructure Au@PtTi are similar to the synthesis conditions of Au@PtV nanostructure, except that V(acac)3 is replaced by titanium oxide acetylacetonate and the reaction temperature is increased to 195°C.

[0059] In one embodiment, 4H / fcc core-shell Au@PtV heterostructures can be synthesized using platinum (II) acetylacetonate and vanadium (III) acetylacetonate as metal precursors, mixed oleylamine and 1-octadecene as solvents, tetrabutylammonium bromide as surfactants, ascorbic acid as reducing agents, and 4H / fcc gold nanorods as seeds.

[0060] Regarding the characterization, Figure 4 The characterization results of 4H / fcc core-shell Au@PtV heterostructure are shown. Figure 4 Part (a) is the TEM image of 4H / fcc core-shell Au@PtV nanorods; Figure 4 Part (b) is a typical TEM image of 4H / fcc core-shell Au@PtV nanorods; Figure 4 Part (c) is a high-resolution TEM image of 4H / fcc core-shell Au@PtV nanorods, where the white arrows show the abundant atomic gaits on the surface; Figure 4 Part (d) is the STEM image of 4H / fcc core-shell Au@PtV nanorods and the corresponding EDS element results; Figure 4 Part (e) is a typical high-resolution HAADF-STEM image after chromatic aberration correction, which shows the atomic structure of 4H / fcc core-shell Au@PtV nanorods; Figure 4The part (e1)-(e4) is from Figure 4 The FFT image obtained in the dotted box in part (e); Figure 4 The part (f) is Au along the

[0004] 4H direction (taken from Figure 4 The oblique rectangular area in the part (e1) and platinum vanadium PtV (which is taken from Figure 4 An example graph of the integrated pixel intensity of the oblique rectangular area in part (e2).

[0061] Figure 5 According to some embodiments of the present invention, characterization diagrams of products obtained under reaction conditions similar to those of 4H / fcc core-shell Au@PtV heterostructures are shown, except that 4H / fcc gold nanorods are not added, wherein Figure 5 Part (a) is an exemplary TEM image; Figure 5 Part (b) of FIG. 5 is an exemplary high-resolution TEM image showing fcc platinum dendrites and no vanadium in the product according to ICP-OES analysis. Figure 6 The XRD patterns of the products obtained under reaction conditions similar to those of the 4H / fcc core-shell Au@PtV heterostructure are shown, where the peaks show a good match with fcc platinum (JCPDS: 70-2075). Figure 7 According to some embodiments of the present invention, further characterization of the product is shown, wherein Figure 7 Part (a) is an exemplary HAADF-STEM image of a typical 4H / fcc core-shell Au@PtV nanorod; Figure 7 Part (b) is obtained by Figure 7 Example line scan of 4H / fcc core-shell Au@PtV nanorods taken with the white line in part (a); Figure 7 Part (c) is an exemplary STEM-EDS spectrum of the 4H / fcc core-shell Au@PtV heterostructure. Figure 8 An example XPS spectrum of a 4H / fcc core-shell Au@PtV heterostructure is shown, which shows that some gold 4f ( Figure 8 of (a)), platinum 4f ( Figure 8 part (b)) and vanadium 2p ( Figure 8 Energy spectrum peak of part (c)).

[0062] Figure 4 The TEM images in parts (a) and (b) show the morphology of 4H / fcc core-shell Au@PtV nanorods, where the gold nanorods are capped by a PtV shell with an average thickness of 4.2 ± 0.9 nm. Note that fcc Pt dendritic nanoparticles were formed under the same conditions except that there was no gold seed, which can be seen in Figure 2. Figure 5 and Figure 6 As shown. The surface of the 4H / fccPtV shell has abundant atomic steps and corners, such as Figure 4 STEM-EDS element distribution map (see Figure 4 Part (d) shows the atomic distribution of gold Au, platinum Pt and vanadium V, confirming the formation of core-shell heterostructure. Figure 4 The spherical aberration-corrected HAADF-STEM image in part (e) shows the atomic structure of the 4H / fcc core-shell Au@PtV heterostructure. The continuous lattice fringes illustrate the epitaxial growth relationship between the shell and the core. Figure 4 The corresponding FFT patterns in parts (e1)-(e4) of the Figure 4 confirm the existence of the 4H / fcc unconventional phase in the core-shell Au@PtV heterostructure. The integrated pixel intensity of the (0004) 4H lattice is also calculated and displayed, as shown in Figure 4. Figure 4 As shown in part (f), in region e1 of the gold nanorod, the average lattice spacing of (0004)4H is In region e2 of the platinum-vanadium alloy, The introduction of vanadium can lead to lattice compression of 4H platinum nanostructures, which is consistent with previous research results on platinum-based nanomaterials. Figure 7 ) further shows the element distribution of the 4H / fcc core-shell Au@PtV heterostructure. The atomic ratio of Au:Pt:V is 66.1:25.9:8.0 as measured by ICP-OES, indicating that the ratio of Pt:V is about 3.2. In addition, XPS confirms the presence of metallic states of Au and Pt (see Figure 8 ), and shows the metallic and oxidized states of vanadium (V 3 + ), which may be due to the surface oxidation of vanadium when exposed to air.

[0063] In one embodiment, oleylamine, which can act as both a solvent and a reducing agent, is used to synthesize the 4H / fccAu@PtV heterostructure, and a large amount of tetrabutylammonium bromide is used as a surfactant.

[0064] Regarding its characterization, Fig. 9 The characterization diagram of the 4H / fccAu@PtV heterostructure according to some embodiments of the present invention is shown, wherein Fig. 9 Part (a) is an exemplary TEM image of 4H / fccAu@PtV nanorods; Fig. 9 Part (b) is an exemplary STEM image of a typical 4H / fccAu@PtV nanorod; Fig. 9 Part (c) is an example high-resolution TEM image of 4H / fccAu@PtV nanorods; Fig. 9Part (d) is the STEM image and its corresponding EDS element distribution map; Fig. 9 Part (e) is a high-resolution HAADF-STEM image of an exemplary 4H / fccAu@PtV nanorod after spherical aberration correction; Fig. 9 Parts (e1) and (e2) are from Fig. 9 An example FFT image obtained in the corresponding dashed square in part (e); Fig. 9 The part (f) is Au along the

[0004] 4H direction (from Fig. 9 The lateral rectangular area in the part (e1) and platinum vanadium PtV (from Fig. 9 An example graph of the integrated pixel intensity of the lateral rectangular area in the portion (e2); Fig. 9 Part (g) is a high-resolution HAADF-STEM image of an exemplary 4H / fccAu@PtV nanorod after spherical aberration correction, which shows the fcc twin structure in the tiny PtV nanorod, and the broken line marks the fcc twin boundary in the platinum vanadium nanorod; Fig. 9 The parts (g1) and (g2) are from Fig. 9 An example image obtained from the corresponding dotted square in part (g).

[0065] Fig.10 Further characterization of the product according to some embodiments of the present invention is shown, wherein Fig.10 Part (a) is an exemplary STEM image of 4H / fccAu@PtV nanorods; Fig.10 Part (b) is an example statistical analysis of the length of PtV nanorods in 4H / fccAu@PtV heterostructures. Fig.11 Further characterization of the products obtained under similar reaction conditions as the 4H / fccAu@PtV heterostructure is presented, with the difference that no vanadium precursor was added, where Fig.11 Part (a) is an exemplary TEM image; Fig.11 Part (b) is an example high resolution TEM image showing the smooth surface of the product. Fig.12 Further characterization of the product according to some embodiments of the present invention is shown, wherein Fig.12 Part (a) is an exemplary HAADF-STEM image of a representative 4H / fccAu@PtV nanorod; Fig.12 Part (b) is along Fig.12 Example corresponding STEM-EDS line scan profile taken with white lines in part (a); Fig.12 Part (c) is an exemplary STEM-EDS spectrum of the 4H / fccAu@PtV heterostructure. Fig.13An exemplary XPS spectrum of the 4H / fccAu@PtV heterostructure is shown, which shows that some of the gold 4f ( Fig.13 of (a)), platinum 4f ( Fig.13 part (b)) and vanadium 2p ( Fig.13 Energy spectrum peak of part (c)). Fig.14 An exemplary comparison of the platinum 4f energy spectrum peaks of 4H / fcc Au@Pt and 4H / fcc Au@PtV heterostructures in XPS spectra is shown.

[0066] Fig. 9 TEM image of part (a) and Fig. 9 The STEM image in part (b) shows the morphology of the 4H / fccAu@PtV heterostructure. Tiny PtV nanorods can be grown vertically on the 4H / fcc Au nanorods (see Fig. 9 The average length of the part (c) was measured to be 4.0 ± 1.0 nm (see Fig.10 ). It is noteworthy that the atomic ratio of Au:Pt:V is similar to that of the 4H / fcc core-shell Au@PtV heterostructure, which is 62.5:27.9:9.6 as measured by ICP-OES. Such results provide potential for studying the shape-related properties of the 4H / fcc core-shell Au@PtV heterostructure. Fig. 9 Part (d) shows the atomic distribution of gold, platinum, and vanadium in the 4H / fccAu@PtV heterostructure. Fig. 9 Part (e) and Fig. 9 The corresponding FFT patterns in sections (e1) and (e2) of the Au nanorods reveal a continuous lattice texture from the 4H phase of the Au seed to the overlying PtV alloy, confirming the epitaxial growth relationship. Compared with the 4H / fcc core-shell Au@PtV heterostructure, the average lattice spacing of (0004)4H increases from that in region e1 to that in region 2. Change to the region e2 of the platinum-vanadium alloy (See Fig. 9 Part (f) shows that the PtV lattice is compressed at (0004)4H. In addition, PtV nanorods also have fcc twin structures and can be grown on 4H / fcc gold nanorods, such as Fig. 9 Part (g) and Fig. 9 The corresponding FFT patterns in parts (g1) and (g2) of FIG. 4 are shown. Basically, the 4H phase and the fcc twin interface may have different surface energies compared to the defect-free fcc, and therefore, if the reaction conditions can be finely tuned, they can serve as preferential growth sites for the formation of heterostructures of tiny Pt-V nanorods. In addition, it was demonstrated that trivalent vanadium ketoacetate palladium is a necessary component for the formation of this type of heterostructure (see Fig.11 ). EDS line scan (see Fig.12) also shows the elemental distribution of gold, platinum, and vanadium in the 4H / fccAu@PtV heterostructure. In addition, the XPS spectra of gold 4f and platinum 4f confirm the metallic state of gold and platinum elements. In the vanadium 2P spectrum, the metallic and oxidized states (V 4+ ), indicating that vanadium surface oxidation has occurred in the resulting 4H / fccAu@PtV heterostructure. More importantly, the Pt 4f peaks of 4H / fcc Au@Pt, 4H / fcc core-shell Au@PtV, and 4H / fcc Au@PtV were further compared (see Fig.14 ). The Pt 4f peak of 4H / fcc Au@PtV can shift to higher binding energy, indicating a change in the electronic structure of Pt. This positive shift of the Pt 4f peak may be caused by the lattice compression of 4H PtV, as shown in Figure 2 , Figure 4 and Fig. 9 The average lattice spacing change of (0004)4H is shown in FIG.

[0067] In one embodiment, the synthetic process employed can also form 4H / fcc platinum-titanium alloy under mild conditions with controllable morphology.

[0068] Regarding the characterization of 4H / fcc Au@PtTi heterostructures, Fig.15 The characterization of 4H / fcc Au@PtTi heterostructures according to some embodiments of the present invention is shown, wherein Fig.15 Part (a) is an exemplary TEM image of 4H / fcc core-shell Au@PtTi nanorods; Fig.15 Part (a) is an exemplary STEM image of a representative 4H / fcc core-shell Au@PtTi nanorod and its corresponding EDS element distribution map; Fig.15 Part (c) is an exemplary high-resolution TEM image of 4H / fcc core-shell Au@PtTi nanorods, and the white arrows show the abundant atomic steps on its surface; Fig.15 The part (c1)-(c4) is from Fig.15 An exemplary FFT image obtained in the corresponding dashed square in part (c).

[0069] Fig.16 The XPS spectrum of the 4H / fcc core-shell Au@PtTi heterostructure is shown, and the energy spectrum peaks of gold 4f, platinum 4f and titanium 2p are shown in parts (a), (b) and (c) of the accompanying figure, respectively. Fig.17 According to some embodiments of the present invention, 4H / fcc Au@PtTi heterostructures are further characterized, wherein Fig.17 Part (a) is an exemplary TEM image of 4H / fccAu@PtTi nanorods; Fig.17 Part (b) is a typical example STEM image of 4H / fccAu@PtTi nanorods; Fig.17 Part (c) is an exemplary STEM image and the corresponding EDS element distribution map; Fig.17 Part (d) is an exemplary high-resolution TEM image of a representative 4H / fccAu@PtTi nanorod; Fig.17 The parts (d1) and (d2) are from Fig.17 An exemplary FFT image obtained in the corresponding dashed square in part (d); Fig.17 Part (e) is an exemplary high-resolution TEM image of an exemplary 4H / fccAu@PtTi nanorod, which shows the fcc twin structure in the tiny platinum-titanium nanorods; Fig.17 Parts (e1) and (e2) are from Fig.17 An exemplary FFT image acquired in the corresponding dashed square in part (e). Fig.18 The XPS spectrum of the 4H / fccAu@PtTi heterostructure is shown, and parts (a), (b) and (c) of the accompanying figure show the energy spectrum peaks of gold 4f, platinum 4f and titanium 2p, respectively.

[0070] Fig.15 Parts (a) and (b) show the morphology and element distribution of the 4H / fcc core-shell Au@PtTi heterostructure. The atomic ratio of gold, platinum, and titanium was measured to be 66.4:27.4:6.2 by ICP-OES. Fig.15 The high-resolution TEM image of part (c) and the corresponding FFT pattern confirm the 4H / fcc unconventional phase structure. XPS further reveals the chemical states of gold, platinum and titanium (see Fig.16 By carefully adjusting the reaction conditions, the morphology of 4H / fcc Au@PtTi can be precisely controlled to form 4H / fccAu@PtTi heterostructures (see Fig.17 STEM-EDS elemental mapping shows the growth of tiny Pt-Ti nanorods on gold nanorods (see Fig.17 The atomic ratio of gold, platinum and titanium was measured by ICP-OES to be 58.1:33.2:8.7. The platinum-titanium nanorods exhibited 4H and fcc twin structures, which can be seen from the high-resolution TEM images (see Fig.17 (d) and (e)) and the corresponding FFT patterns (see Fig.17 The XPS spectrum shows the chemical states of gold, platinum and titanium in the 4H / fccAu@PtTi heterostructure (see Fig.18 ).

[0071] Heterostructures based on noble metals are promising catalysts in hydrogen evolution reaction, oxygen reduction reaction (ORR) and alcohol oxidation reaction (AOR); therefore, as a proof-of-concept application, 4H / fcc Au@Pt and 4H / fcc Au@PtV heterostructures were used as electrocatalysts for electrochemical methanol oxidation reaction (MOR) and ethanol oxidation reaction (EOR) in alkaline media. Commercial Pt / C catalysts and 4H / fcc gold nanorods were also compared. For electrochemical measurements, a three-electrode system at room temperature was used as described below.

[0072] For the three-electrode system, this section will provide the preparation method of its electrode. 400μg Vulcan XC-72R carbon black was dispersed in 1 ml of ethanol in a 4 ml vial and treated with ultrasound in an ice bath for 1 hour to ensure the formation of a uniform suspension. Subsequently, a catalyst solution containing 100μg of platinum element, as determined by ICP-OES, was added dropwise to the carbon suspension. Then, it was treated with ultrasound again in an ice bath for 1 hour. After that, the resulting catalyst / carbon (catalyst / C) was collected by centrifuging the mixture at 10000rpm for 5 minutes, and then washed five times with a mixture of chloroform and ethanol (2 ml). Then, the catalyst / C containing 100μg of platinum was redispersed in a mixed solution of isopropanol (693 microliters) and Milli-Q water (297 microliters). Subsequently, 10μL of Nafion solution (5%) was added to the mixture, which was then treated with ultrasound for 30 minutes. 10 μL of the resulting solution was dripped onto a glassy carbon electrode (GCE, 5 mm in diameter) to prepare a working electrode, which was pre-polished with alumina slurry and then washed with Milli-Q water and ethanol to achieve a platinum loading of 5.1 μg*cm -2 The obtained electrode was dried under ambient conditions until the solvent was completely evaporated.

[0073] In the electrochemical measurements, the catalyst-coated GCE working electrode, Pt wire, and mercury / mercury oxide (Hg / HgO) electrode described in this paper were used as the working electrode, counter electrode, and reference electrode, respectively. The Hg / HgO electrode was calibrated according to the reversible hydrogen electrode (RHE). Before the electrocatalytic measurements, cyclic voltammetry (CV) was performed in a 1.0 M KOH electrolyte saturated with N2 at a potential range of 0.05–1.20 V (vs. RHE) to remove the ligands on the catalyst surface. The CV was performed at 50 mV s in a 1.0 M KOH aqueous solution saturated with N2 and containing 1.0 M methanol or 1.0 M ethanol. -1The MOR or EOR performance was tested at a scan rate of 1.0 M. The catalytic durability for MOR or EOR was tested by constant current measurement at 0.78 V or 0.77 V (vs. RHE) in a 1.0 M KOH aqueous solution saturated with N2 containing 1.0 M methanol or ethanol.

[0074] The electrochemically active surface area (ECSA) of the catalyst was determined by underpotential hydrogen desorption in 1.0 M KOH solution. Specifically, the ECSA can be calculated according to the following equation:

[0075] Among them, Q H-desorption represents the charge associated with the desorption of hydrogen from the platinum surface in the hydrogen desorption region on the CV curve, and m represents the mass load of platinum (i.e., 1×10 -6 g), and 210 μC cm -2 The value of is a reference value for the charge of full coverage on a clean platinum surface.

[0076] Fig.19 shows example results of electrochemical measurements, where Fig.19 Part (a) shows the scanning rate of 50 mV s in 1.0 M KOH aqueous solution saturated with N2. -1 Pt mass-normalized CV curves of 4H / fcc Au@Pt, 4H / fcc core-shell Au@PtV, 4H / fccAu@PtV, commercial Pt / C, and 4H / fcc gold nanorods at . Fig.19 Part (b) shows the mass activity at the corresponding peak in the CV curve; Fig.19 Part (c) shows the ECSA normalized curve of the CV curve; Fig.19 Part (d) shows the specific activity at the corresponding peak in the CV curve; Fig.19 Part (e) shows the chronoamperometric measurements of durability evaluation performed at 0.78 V vs RHE in 1.0 M KOH aqueous solution saturated with N2; Fig.19 Part (f) shows the scanning rate of 50 mV s in 1.0 M KOH aqueous solution saturated with N2. -1 The normalized mass activity of platinum is obtained when “j” and “j m ” represent specific current density and mass current density, respectively.

[0077] To this end, first, 1.0 M methanol was contained in a 1.0 M KOH solution saturated with N2, and cyclic voltammetry (CV) curves were recorded to estimate its catalytic methanol oxidation reaction (MOR) activity. Fig.19 As shown in part (a), compared with other catalysts, 4H / fcc Au@PtV heterostructures exhibit the highest platinum mass normalized current density in a wide potential range of 0.5-1.2 V (vs. reversible hydrogen electrode (RHE)), while 4H / fcc gold nanorods have almost no activity. Furthermore, the mass activities of 4H / fccAu@Pt, 4H / fccAu@PtV heterostructures and commercial Pt / C catalysts at their peak MOR were further calculated (see Fig.19 Part (b) of Figure 2). It is worth noting that the 4H / fcc Au@PtV catalyst shows 8.33AmgPt -1 The highest mass activity of Au@PtV is 2.36A mg Pt -1 )、Au@Pt(1.29A mg Pt -1 ) and commercial Pt / C (0.87A mg Pt -1 The mass activity of 4H / fcc Au@PtV heterostructures is also superior to that of most prior art Pt-based catalysts, as shown in Table I below. Table I: Comparison of the electrocatalytic performance of platinum-based catalysts for MOR in related works and the present disclosure. [a]: Mass normalized peak current (A mg) for Pt and Pd Pt+Pd -1 ).

[0078] Fig. 20 Cyclic voltammetry (CV) curve examples are shown, and the (a), (b), (c), and (d) parts of the accompanying drawings are 4H / fcc Au@PtV heterostructures, 4H / fcc core-shell Au@PtV heterostructures, 4H / fcc Au@Pt heterostructures, and commercial Pt / C. To find out their intrinsic catalytic activity, the specific activity of the platinum-based catalyst can be calculated by normalizing its current to the corresponding electrochemically active surface area (ECSA). Fig. 20 As shown in Figure 2, the CV curves of the 4H / fcc Au@PtV heterostructures show stronger hydrogen absorption peaks than those of the 4H / fcc core-shell Au@PtV, 4H / fcc Au@Pt, and Pt / C catalysts. The ECSA of the 4H / fcc Au@PtV heterostructure is calculated to be 52.1 m 2 g pt-1 , which are 4H / fcc core-shell Au@PtV(29.6m 2 g pt -1 )、4H / fcc Au@Pt(18.7m 2 g pt -1 ) and commercial Pt / C (46.4m 2 g pt -1 ) is 1.8, 2.8 and 1.1 times. Fig.19 As shown in part (c), the 4H / fcc Au@PtV heterostructure still exhibits the highest ECSA normalized current density in a wide potential range. -2 )<4H / fcc Au@Pt(6.42mA cm -2 )<4H / fcc core-shell Au@PtV(7.96mAcm -2 )<4H / fcc Au@PtV(15.99mA cm -2 ) in increasing order (e.g. Fig.19 Such results indicate that the unconventional phase structure, the introduction of vanadium and the core-shell morphology can significantly promote the intrinsic catalytic behavior of Pt catalysts.

[0079] Fig.21 An example of durability evaluation of the 4H / fcc Au@PtV heterostructures by chronoamperometry testing in N2-saturated 1.0 M KOH aqueous solution containing 1.0 M methanol at 0.78 V vs RHE is shown. The current density of the commercial Pt / C catalyst drops rapidly within the first 3600 s. Fig. 22 Figure 4 shows the characterization of the 4H / fcc Au@PtV heterostructure after the methanol oxidation reaction (MOR) stability test (14400 s). Fig. 22 Part (a) is an exemplary TEM image of the carbon-loaded 4H / fccAu@PtV heterostructure; Fig. 22 Part (b) is a high-resolution TEM image of a typical 4H / fcc Au@PtV nanorod and its corresponding FFT pattern example; Fig. 22 Part (c) is an exemplary EDS spectrum diagram of the 4H / fcc Au@PtV heterostructure after stability test; Fig. 22 Part (d) is a comparative example diagram of the atomic ratios (at. %) of gold, platinum, and vanadium in the 4H / fcc Au@PtV heterostructure before and after the MOR stability test based on ICP-OES.

[0080] In addition to electrocatalytic activity, durability is also an important factor for the methanol oxidation reaction (MOR). Herein, the stability of 4H / fcc Au@Pt, 4H / fcc Au@PtV heterostructures, and commercial Pt / C was evaluated by chronoamperometry measurements over 3600 s. Fig.19 As shown in part (e) of the graph, the 4H / fcc Au@PtV heterostructure exhibits better stability than other catalysts. After 3600 seconds, it still maintains a high mass activity of 1.51 A mg Pt –1 , respectively 4H / fcc core-shell Au@PtV(0.36A mg Pt –1 )、4H / fcc Au@Pt(0.17A mg Pt –1 ) and Pt / C(0.12Amg Pt –1 ) catalysts. It is worth noting that after 14400 seconds of testing, the mass activity of 4H / fcc Au@PtV still remained at 0.47 A mg Pt –1 ,like Fig.21 As shown in Figure 2, it further confirms the superior durability against MOR. In addition, after the chronoamperometry test, the 4H / fcc Au@PtV catalyst was recollected and characterized by TEM and EDS, as shown in Figure 2. Fig. 22 The results show that the morphology and composition have almost no change after long-term chronoamperometry testing, which indicates that the 4H / fccAu@PtV heterostructure has excellent structural stability.

[0081] Fig.23 Exemplary results of electrochemical testing are shown, where Fig.23 Part (a) shows the N2-saturated 1.0 M KOH aqueous solution containing 1.0 M ethanol at 50 mV s -1 ECSA normalized CV curves of 4H / fcc Au@Pt, two 4H / fcc Au@PtV heterostructures and commercial Pt / C at a scan rate of 1.34°; Fig.23 Part (b) shows the specific activities of 4H / fcc Au@Pt and two 4H / fcc Au@PtV heterostructures and commercial Pt / C in the CV curves, with their corresponding peak potentials as references; Fig.23Part (c) shows the durability evaluation of 4H / fcc Au@Pt and two 4H / fcc Au@PtV heterostructures and commercial Pt / C by chronoamperometry testing in N2-saturated 1.0 M KOH aqueous solution containing 1.0 M ethanol at 0.77 V vsRHE.

[0082] In addition to MOR, the electrocatalytic performance of 4H / fcc Au@Pt and 4H / fcc Au@PtV heterostructures for ethanol oxidation reaction (EOR) was also investigated. Fig.19 Part (f) of Fig.23 As shown in Table II below. The 4H / fcc Au@PtV heterostructure exhibits the highest mass activity of 6.12 A mg Pt –1 ( Fig.19 (f) of the 4H / fcc core-shell Au@PtV (1.57Amg Pt –1 )、4H / fcc Au@Pt(0.80A mg Pt –1 ) and Pt / C(0.59A mg Pt –1 ) catalysts, and also outperformed many representative platinum-based catalysts for EOR, which can be seen in Table II. In addition, the 4H / fcc Au@PtV heterostructure also exhibited excellent specific activity for EOR, with the highest 11.74 mA cm-2 achieved on the 4H / fcc Au@PtV heterostructure. -2 The specific activity (see Fig.23 (b)). In addition, after 3600 seconds of testing, the 4H / fccAu@PtV heterostructure can still maintain 0.072A mg Pt –1 The mass activity (see Fig.23 (c)), while the mass activities of other catalysts are negligible, which indicates that the 4H / fcc Au@PtV heterostructure can have superior electrocatalytic stability. Table II: Comparison of electrocatalytic performance of platinum-based catalysts for EOR in related works and the present invention. [a]: Mass normalized peak current (A mg) of Pt and Pd / Rh Pt+Pd / Rh -1 ).

[0083] Fig.24The real-time operation of the 4H / fcc Au@PtV catalyst during electrochemical MOR was shown by infrared reflection absorption spectroscopy (IRAS) (see Fig.24 (a) to (c) of Fig.24 Parts (d) to (f) show the real-time operation infrared reflection absorption spectroscopy (IRAS) spectra of the 4H / fcc core-shell Au@PtV catalyst undergoing electrochemical MOR in an aqueous solution containing 1.0 M methanol and 1.0 M KOH. Fig.25 Real-time in-operation infrared reflection absorption spectroscopy (IRAS) study of the electrochemical MOR of 4H / fcc Au@Pt nanorods is shown.

[0084] In order to gain a deeper understanding of the reaction mechanism and product selectivity during the MOR process, 4H / fcc Au@PtV (see Fig.24 (a) to (c)), 4H / fcc core-shell Au@PtV (see Fig.24 (d) to (f) of 4H / fcc Au@Pt (see Fig.25 (a), (b), (c) of the present invention) were studied by real-time infrared reflection absorption spectroscopy (IRAS). MOR can usually be carried out through CO or non-CO pathways. In the CO pathway, CO oxidation to CO2 is the last step in the complete oxidation of methanol. In the non-CO pathway, formic acid is a reaction intermediate, and the activation energy of formic acid conversion to CO2 is lower than that of CO oxidation, which is more conducive to MOR. Fig.24 As shown in parts (a) and (d) of the graph, a linearly adsorbed CO (COL) species was observed on the 4H / fcc Au@PtV catalyst at ∼2100 cm -1 This indicates that CO is a reaction intermediate on the 4H / fcc Au@PtV catalyst. Fig.24 As shown in parts (b) and (e), at about 1645 cm -1 The band at may be the bending mode of interfacial water, which may facilitate the generation of oxidative species (e.g., OH). The OH species adsorbed on the catalyst surface promote CO oxidation, thereby alleviating the poisoning effect of Pt, and thus improving the MOR performance. Fig.24 As shown in parts (c) and (f) of Figure 3, the characteristic peaks contribute to the asymmetric stretching vibration of CO2, which indicates the complete oxidation of methanol during the six electron transfer process on the 4H / fcc Au@PtV catalyst. It is worth noting that for the 4H / fcc Au@PtV catalyst, the peak at ∼1341 cm -1 The band at can be attributed to the bridged formate (HCOO B ), indicating that methanol oxidation on 4H / fcc Au@PtV catalyst proceeds through both CO and non-CO pathways. Fig.24 As shown in part (e), there is no HCOO on the 4H / fcc core-shell Au@PtV catalyst. B This indicates that methanol oxidation follows the CO pathway on the 4H / fcc Au@PtV catalyst. The methanol oxidation reaction pathway on the 4H / fcc Au@Pt catalyst is similar to that on the 4H / fcc Au@PtV catalyst (see Fig.25 For the 4H / fcc Au@PtV heterojunction, the generated HCOO B The intermediates can promote the cleavage of C—H bonds to produce CO2 with low activation energy and fast kinetics. The existence of non-CO pathways explains the larger current density of electrochemical MOR on 4H / fcc Au@PtV catalysts.

[0085] Fig.26 The X-ray diffraction (XRD) characterization results of 4H / fcc gold nanorods, 4H / fcc Au@Pt, 4H / fcc core-shell Au@PtV and 4H / fcc Au@PtV catalysts are shown, where all XRD patterns were collected in θ / 2θ mode.

[0086] The superior electrocatalytic performance of the 4H / fcc Au@PtV heterostructure can also be attributed to the following reasons. First, the Au@PtV heterostructure crystallizes in the 4H / fcc unconventional phase, which has a large number of crystal phase boundaries (see Fig.26 ), which can serve as additional catalytic active sites, thereby enhancing the alcohol oxidation activity. Secondly, in the 4H / fcc Au@PtV heterostructure, there are multiple branches with 4H phase and fcc twin boundaries (see Fig. 9 ), which can provide abundant active sites for methanol oxidation and ethanol oxidation (see Fig. 20 ). Third, compared with Pt(0004)4H in 4H / fcc Au@Pt and PtV(0004)4H in 4H / fcc core-shell Au@PtV heterostructures, the lattice compression of PtV(0004)4H in 4H / fcc Au@PtV catalyst can be clearly observed in HAADF-STEM images (see Fig. 9 ). This lattice change can also adjust its electronic structure, as shown in the XPS spectrum of platinum 4f (see Fig.14 ). The modified lattice and electronic structure can change the adsorption interaction with the intermediates during alcohol oxidation, thereby promoting the improvement of catalytic activity.

[0087] Fig. 27A flow chart for synthesizing heterogeneous catalysts is illustrated, involving a general method for using them for alcohol oxidation reactions in direct alcohol fuel cells anode reactions. Herein, a general method for synthesizing 4H / fcc unconventional phase platinum-based nanocatalysts is provided, which can serve as efficient heterogeneous catalysts for the essential anode reaction in direct alcohol fuel cells (DAFCs), namely, the alcohol oxidation reaction (AOR) under alkaline conditions. Specifically, the synthesized 4H / fcc unconventional phase platinum-based nanocatalysts, especially 4H / fcc Au@PtV nanomaterials, exhibited good electrocatalytic performance for alcohol oxidation reactions, showing high activity and excellent long-term stability. These findings are helpful for the development of advanced electrocatalysts with practical applications. In addition, the synthesized unconventional phase platinum-based nanomaterials showed greater advantages than existing catalysts in various catalytic reactions, including electrocatalytic reactions. For example, in the case of electrochemical methanol oxidation reaction (MOR), platinum-based noble metals such as platinum and palladium are widely regarded as efficient catalysts.

[0088] The synthesis method (ie, the synthesis process) includes at least steps 102, 104, 106 and 108, which can be used as general stages, wherein the method can also include other steps or adjust different reaction conditions to adjust the core-shell morphology.

[0089] In step 102, a material A selected from platinum (II) bis (acetylacetonate), vanadium (III) acetylacetonate and titanium oxide acetylacetonate is mixed with a solvent B selected from oleylamine and 1-octadecene to form a first mixture. In step 104, a dispersion C of 4H / fcc gold nanorods is added to the first mixture to form a second mixture. In some embodiments, the contents of A, B and C are all positive values, wherein the ratio of A to B is in the range of 0.5 to 2, and the ratio of A to C is in the range of 2 to 6. In step 106, the second mixture is heated to a temperature in the range of 150°C to 200°C and the duration is in the range of 5 hours to 15 hours. In step 108, the product is recovered from the second mixture to obtain a 4H / fcc platinum-based heterostructure with gold. Specifically, the product of the synthesis process includes at least one platinum-based nanorod deposited on a gold nanorod with a 4H / fcc unconventional phase.

[0090] For the synthesis of 4H / fcc core-shell Au-Pt heterostructures, 2.0 mg of diacetylacetonate platinum (II) (Pt(acac)2) and 20.0 mg of ascorbic acid can be added to a 15 ml Schlenk tube containing 2.0 ml of oleylamine to form a first mixture. Subsequently, the first mixture can be ultrasonically treated for 30 minutes. Thereafter, 0.75 ml of pre-prepared 4H / fcc gold nanorods (which are a mixture dispersed in hexane) are added to the first mixture to form a second mixture. The Schlenk tube with the second mixture is then evacuated at room temperature for 30 minutes and ventilated with nitrogen under magnetic stirring. Subsequently, the second mixture is heated to 170°C and maintained for 5 hours. Finally, the resulting product is washed 3 times by centrifugation in a mixture of hexane and ethanol at a speed of 5000 rpm for 3 minutes. In some embodiments, during the synthesis process, platinum-based nanorods can be epitaxially grown from gold nanorods to form a 4H / fcc core-shell Au-Pt heterostructure with gold nanorods as seeds. In some embodiments, platinum-based nanorods can form a platinum shell with an average thickness of 4.2 nm to 5.2 nm on the gold nanorods.

[0091] In an embodiment involving the synthesis of 4H / fcc core-shell Au-PtV heterostructures, a first mixture is formed by mixing platinum (II) bis (acetylacetonate) and vanadium (III) acetylacetonate in a weight ratio ranging from 0.5 to 1. For example, for the synthesis of 4H / fcc unconventional phase Au@PtV nanomaterials, 2.0 ml of 1-octadecene is first mixed with 2.0 ml of oleylamine in a 15 ml Schlenk tube. Then, 2.0 mg of Pt(acac)2, 4.0 mg of V(acac)3, and 20.0 mg of ascorbic acid are added to the solution to form a first mixture. Subsequently, the first mixture is sonicated for 30 minutes. Thereafter, 2.0 mg of tetrabutylammonium bromide and 0.75 ml of a pre-prepared 4H / fcc gold nanorod dispersion (which is dispersed in hexane) are added to the first mixture to form a second mixture. The Schlenk tube with the second mixture is vacuum evacuated for 30 minutes and ventilated with nitrogen under magnetic stirring. Then, the second mixture was heated to 180°C and maintained for 5 hours. Finally, the resulting product was washed 3 times by centrifugation in a mixture of hexane and ethanol at a speed of 5000 rpm for 3 minutes. In some embodiments, during the synthesis process, platinum-based nanobranch (which includes vanadium) can be epitaxially grown from gold nanorods to form a 4H / fcc core-shell Au-PtV heterostructure with gold nanorods as seeds. In some embodiments, platinum-based nanobranch can form a platinum-vanadium shell with an average thickness of 3.3 nm to 5.1 nm on the gold nanorods.

[0092] In an embodiment involving the synthesis of 4H / fcc core-shell Au-PtTi heterostructures, a first mixture is formed by mixing platinum(II) bis(acetylacetonate) and titanium oxide acetylacetonate in a weight ratio ranging from 0.5 to 1. In this regard, the synthesis conditions of the 4H / fcc unconventional phase Au@PtTi heterostructure are similar to those of the Au@PtV nanostructure, except that V(acac)3 is replaced with titanium oxide acetylacetonate and the reaction temperature is increased to 185°C. Platinum-based nanorods containing titanium can be epitaxially grown from gold nanorods to form 4H / fcc core-shell Au-PtTi heterostructures seeded with gold nanorods.

[0093] In an embodiment involving the synthesis of 4H / fcc unconventional phase Au-PtV heterostructures, platinum (II) bis (acetylacetonate) and vanadium (III) acetylacetonate are first mixed in a weight ratio ranging from 0.5 to 1 to form a first mixture. For example, for the synthesis of 4H / fcc unconventional phase Au@PtV heterostructures, 2.0 mg of Pt(acac)2 and 3.0 mg of V(acac)3 are added to a 15 ml Schlenk tube containing 2.0 ml of oleylamine to form a first mixture. Subsequently, the first mixture is ultrasonically treated for 30 minutes. Then, 5.0 mg of tetrabutylammonium bromide and 0.75 ml of pre-prepared 4H / fcc gold nanorods dispersed in hexane are added to the first mixture to form a second mixture. The Schlenk tube containing the second mixture is evacuated at room temperature for 30 minutes to remove the hexane under magnetic stirring. The second mixture is heated to 190°C and maintained for 12 hours. Finally, the resulting product is washed three times with a mixture of hexane and ethanol by centrifugation at 5000 rpm for 3 minutes. In some embodiments, during the synthesis process, platinum-based nanobranch including vanadium can be epitaxially grown from gold nanorods to form 4H / fcc unconventional phase Au-PtV heterostructures, in which gold nanorods can serve as seeds. In some embodiments, platinum-based nanobranch including vanadium extends vertically in a direction different from the longitudinal axis of the gold nanorod (e.g., perpendicular to the longitudinal axis of the gold nanorod), thereby forming platinum-vanadium nanorods on the gold nanorods. In some embodiments, the average length of the grown platinum-vanadium nanorods is in the range of 3 nm to 5 nm.

[0094] In an embodiment involving the synthesis of 4H / fcc unconventional phase Au-PtTi heterostructures, platinum (II) bis (acetylacetonate) and titanium oxide acetylacetonate are first mixed in a weight ratio ranging from 0.5 to 1 to form a first mixture. In this regard, the synthesis conditions of the 4H / fcc unconventional phase Au-PtTi heterostructure are similar to those of the Au@PtV nanostructure, except that V(acac)3 is replaced with titanium oxide acetylacetonate and the reaction temperature is increased to 195°C. Platinum-based nanorods including titanium can be epitaxially grown from gold nanorods to form 4H / fcc unconventional phase Au-PtTi heterostructures, wherein the gold nanorods serve as seeds.

[0095] In some embodiments, the ascorbic acid added to the first mixture can be replaced with glucose of the same molar amount. In some embodiments, octadecylamine can also be used as a solvent. For example, in the stage of preparing the first mixture, the above-mentioned oleylamine or 1-octadecylene can be replaced with octadecylamine of the same molar amount. Here, the selective replacement of additives or solvents can be used to improve the overall versatility and efficiency of the method and make the synthesis process more flexible.

[0096] Through the above structure, the 4H / fcc core-shell Pt-based heterostructure exhibits excellent catalytic performance for electrochemical alcohol oxidation reaction (AOR) under alkaline conditions. On the 4H / fcc Pt-based catalyst, 8.33 and 6.12 mg Pt –1 The high-quality activity of the catalyst can be used for alcohol oxidation reaction (MOR) and alcohol electrooxidation reaction (EOR). In situ infrared reflection absorption spectroscopy shows that the MOR reaction on the same catalyst can proceed through CO and formate pathways and exhibits fast reaction kinetics.

[0097] The foregoing description of the present invention is provided for the purpose of illustration and description. It is not intended to be exhaustive or to limit the present invention to the precise form disclosed. Many modifications and variations will be apparent to those skilled in the art.

[0098] The embodiments were chosen and described in order to best explain the principles of the invention and its practical applications, thereby enabling others skilled in the art to understand the invention for various embodiments and with various modifications as are suited to the particular use contemplated.

Claims

1. A heterogeneous catalyst, characterized in that: include: At least one platinum-based nanobranch is deposited on the gold nanorod by a synthesis process to form a 4H / face-centered cubic (face-centered cubic; fcc) unconventional phase, wherein the synthesis process comprises: mixing a material A selected from platinum (II) bis(acetylacetonate), vanadium (III) acetylacetonate, and titanium oxide acetylacetonate with a solvent B selected from oleylamine and 1-octadecene to form a first mixture; adding the dispersion C of 4H / fcc gold nanorods to the first mixture to form a second mixture; wherein the contents of A, B and C are all positive values, the ratio of A to B is in the range of 0.5 to 2, and the ratio of A to C is in the range of 2 to 6; heating the second mixture to a temperature in the range of 150°C to 200°C for a duration in the range of 5 hours to 15 hours; and The product is recovered from the second mixture to obtain a 4H / fcc platinum-based heterostructure with gold.

2. The heterogeneous catalyst according to claim 1, characterized in that The platinum-based nanobranch forms a platinum shell with an average thickness of 4.2 nm to 5.2 nm on the gold nanorod.

3. The heterogeneous catalyst according to claim 1, characterized in that The platinum-based nanorods include vanadium, which forms a coating of a platinum-vanadium shell layer with an average thickness of 3.3 nm to 5.1 nm on the gold nanorods.

4. The heterogeneous catalyst according to claim 1, characterized in that The platinum-based nanorods include vanadium, which extend perpendicularly from the gold nanorods in a direction different from the longitudinal axis of the gold nanorods, thereby forming platinum-vanadium nanorods on the gold nanorods.

5. The heterogeneous catalyst according to claim 4, characterized in that The average length of the platinum vanadium nanorods is 3 nanometers to 5 nanometers.

6. The heterogeneous catalyst according to claim 1, characterized in that The first mixture is prepared by mixing platinum (II) bis(acetylacetonate) and vanadium (III) acetylacetonate in a weight ratio ranging from 0.5 to 1.

7. The heterogeneous catalyst according to claim 1, characterized in that The first mixture is prepared by mixing platinum (II) bis(acetylacetonate) and titanium oxide acetylacetonate in a weight ratio ranging from 0.5 to 1.

8. The heterogeneous catalyst according to claim 1, characterized in that The first mixture is formed by using a solvent containing oleylamine and 1-octadecene.

9. The heterogeneous catalyst according to claim 1, characterized in that: The first mixture is prepared by mixing the material with ascorbic acid or glucose.

10. The heterogeneous catalyst according to claim 1, characterized in that The synthesis process further comprises subjecting the first mixture to ultrasonic treatment.

11. The heterogeneous catalyst according to claim 1, characterized in that The synthesis method further comprises adding tetrabutylammonium bromide to the second mixture.

12. The heterogeneous catalyst according to claim 1, characterized in that The platinum-based nanobranches are epitaxially grown from the gold nanorods, thereby forming a 4H / fcc core-shell gold-platinum (Au-Pt) heterostructure with the gold nanorods as seeds.

13. The heterogeneous catalyst according to claim 1, characterized in that The platinum-based nanorods also contain vanadium, which grows epitaxially from the gold nanorods to form a 4H / fcc core-shell gold-platinum-vanadium (Au-PtV) heterostructure with the gold nanorods as seeds.

14. The heterogeneous catalyst according to claim 1, characterized in that The platinum-based nanorods further include titanium, which is epitaxially grown from the gold nanorods to form a 4H / fcc core-shell gold-platinum-titanium (Au-PtTi) heterostructure with the gold nanorods as seeds.

15. The heterogeneous catalyst according to claim 1, characterized in that The platinum-based nanorods also contain vanadium, which grows epitaxially from the gold nanorods to form a 4H / fcc unconventional phase core-shell gold-platinum-vanadium (Au-PtV) heterostructure with the gold nanorods as seeds.

16. The heterogeneous catalyst according to claim 1, characterized in that The platinum-based nanorods also include titanium, which is epitaxially grown from the gold nanorods to form a 4H / fcc unconventional phase core-shell gold-platinum-titanium (Au-PtTi) heterostructure with the gold nanorods as seeds.

17. A method for preparing a heterogeneous catalyst, characterized in that: include: mixing a material A selected from platinum (II) bis(acetylacetonate), vanadium (III) acetylacetonate, and titanium oxide acetylacetonate with a solvent B selected from oleylamine and 1-octadecene to form a first mixture; adding the dispersion C of 4H / fcc gold nanorods to the first mixture to form a second mixture; wherein the contents of A, B and C are all positive values, the ratio of A to B is in the range of 0.5 to 2, and the ratio of A to C is in the range of 2 to 6; heating the second mixture to a temperature in the range of 150° C. to 200° C. for a duration in the range of 5 hours to 15 hours; as well as A product is recovered from the second mixture to obtain a 4H / fcc platinum-based heterostructure with gold, which exhibits a 4H / face-centered cubic (fcc) unconventional phase and includes gold nanorods and platinum-based nanobranch deposited on the gold nanorods.

18. The method for preparing a heterogeneous catalyst according to claim 17, characterized in that: The platinum-based nanorods include vanadium, which extend perpendicularly from the gold nanorods in a direction different from the longitudinal axis of the gold nanorods, thereby forming platinum-vanadium nanorods on the gold nanorods.

19. The method for preparing a heterogeneous catalyst according to claim 17, characterized in that: During the synthesis process, the platinum-based nanobranch grows epitaxially from the gold nanorod, thereby forming a 4H / fcc core-shell heterostructure with the gold nanorod as a seed.

20. The method for preparing a heterogeneous catalyst according to claim 17, characterized in that: The platinum-based nanorods further comprise vanadium or titanium, which grows epitaxially from the gold nanorods during the synthesis process, thereby forming a 4H / fcc core-shell heterostructure with the gold nanorods as seeds.